THE IMPACT OF IMPLEMENTING THE FARM TO FORK STRATEGY REGARDING THE USE OF FERTILIZERS AND PESTICIDES IN THE EU - Paula STOICEA; Toma Adrian DINU; Valentina Constanța TUDOR; Mihai GÎDEA; Adina Magdalena IORGA; Irina-Adriana CHIURCIU; Elena SOARE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper analyzes the existing situation in Romania, Germany, France, Poland, Hungary and the United Kingdom, European countries cultivating cereals, technical plants and oleaginous plants, in the period 2010-2019, regarding the quantities of fertilizers and plant protection substances This analysis has responded to the requests from farmers' associations regarding the effect of the FARM TO FORK strategy, as a essential element of the European Green Pact, has serious implications within the agricultural sector. Agricultural producers question the survival of the agricultural sector as the implementation of the Farm to Fork strategy will lead to a significant decrease in agricultural production in the EU and an increase in food prices. In the present study, a descriptive research was performed on the situation existing in each studied country, using the bibliographic method but also the processing of statistical data, using the correlational method, this aspect directing the study to a predictive research, thus establishing how the quantities of fertilizers and pesticides used in different crops in the EU member states will be allocated, if the Farm to Fork strategy is applied in the current form, the conclusion being that their reduction should be applied to the European average of consumption in the EU member states.